Analysis of Waste Transportation Needs for Service Optimization in Bangkinang City District - Alfian Mardani, Bisma; Adeswastoto, Hanantatur; Syifa Tanjung , Lailatul (Journal of Engineering Science and Technology Management, 2025)
Waste transportation is a waste sub-system that aims to bring waste from the location of the transfer of the waste source directly to the Final Disposal Site (TPA). The purpose of this study is to find out the transportation system and waste collection patterns, analyze the transportation needs of waste transportation, and analyze the transportation needs of waste transportation in 2025. The methods used to analyze the transportation needs of waste transportation are the Hauled Container System (HCS) and Stationary Container System (SCS) methods. The data used are regional topographic data, the number of waste transportation equipment, the travel time of waste transportation, and the number of residents in Bangkinang Kota District. The need for garbage carts/pedicabs in 2023 is 61 units and garbage transport vehicles needed for a waste volume of 4.105 tons/day from the Temporary Disposal Site (TPS) to the Final Disposal Site (TPA) consisting of 10 units of tipper trucks measuring 6m³ for 1 trip/day and 1 unit of armroll truck measuring 6m³ with 10 container tubs for 1 trip/day. The need for garbage carts/pedicabs in 2025 is 65 units and garbage transport vehicles in 2025 with a predicted waste volume of 4.105 tons/day is 10 units of tipper trucks measuring 6m³ for 1 ration/day and 1 unit of armroll truck measuring 6m³ for 1 ration/day with 10 container tubs.